VD_FINDINFO Arrêt / 2021 / 614 vom 7. Oktober 2021 - VD Tribunal cantonal (2021)
RENTE D'INVALIDITÉ, RÉVISIONPRESTATION D'ASSURANCE, LOMBALGIE, FIBROMYALGIE, ÉVALUATION DE L'INVALIDITÉ | 28 LAI, 16 LPGA, 17 LPGA, 88a al. 1 RAI